Implementation of Religious Moderation in Islamic Education through the Qur'an Recitation and Reading Program at the Elementary School Level - Rahma Diana Sayidah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: Implementation of Religious Moderation in Islamic Education through the Qur'an Recitation and Reading Program at the Elementary School Level Objective: This study aims to examine the values of religious moderation in the Qur'an recitation and reading program implemented in several elementary schools in Kapanewon Depok, Sleman, Yogyakarta Special Region. Methods: This study used a qualitative approach with a field research design. Data collection techniques included observation, in-depth interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. Data validity was obtained through triangulation of sources and methods. Results: The Qur'an recitation and reading program contains the central values in religious moderation, namely justice (tawasuth), balance (tawazun), and tolerance (Masamune). Conclusion: The Qur'an recitation and reading program is an effective medium in instilling the values of religious moderation in elementary schools. Contribution: This research provides a conceptual and practical basis for developing interfaith education models that strengthen the values of tolerance and diversity in education. INDONESIAN: Penerapan Nilai Moderasi Beragama dalam Pendidikan Islam Melalui Program Mengaji dan Membaca Alkitab pada Jenjang Sekolah DasarTujuan: Penelitian ini bertujuan untuk mengkaji nilai-nilai moderasi beragama yang terkandung dalam program Mengaji dan Membaca Al kitab yang telah diterapkan di beberapa sekolah dasar di Kapanewon Depok, Sleman, Daerah Istimewa Yogyakarta. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan desain penelitian field research. Teknik pengumpulan data meliputi observasi, wawancara mendalam, dan dokumentasi. Data dianalisis melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diperoleh melalui triangulasi sumber dan metode. Hasil: Program Sleman Mengaji dan Membaca Al Kitab memuat nilai-nilai utama dalam moderasi beragama, yaitu keadilan (tawasuth), keseimbangan (tawazun), dan toleransi (tasamuh). Kesimpulan: Program Sleman Mengaji dan Membaca Al kitab menjadi media yang efektif dalam menanamkan nilai-nilai moderasi beragama di sekolah dasar. Kontribusi: Penelitian ini berkontribusi dalam memberikan landasan konseptual dan praktis bagi pengembangan model pendidikan lintas agama yang memperkuat nilai-nilai toleransi dan keberagaman dalam dunia pendidikan.